Business sales driver: A look at promotional campaigns and commercial incentives (International Seven Journal of Multidisciplinary, 2023)
This work studies Promotional Campaigns and Commercial Incentives as drivers of sales in a food company in the interior of São Paulo. However, the present study raises the following question: How do food companies propagate their promotional and incentive campaigns for their employees, in search of increasing their sales and profitability? With this problematization, the general objective of this study is to verify some promotional and incentive campaigns used by food companies towards employees. To achieve the general objective, we have defined the specific objectives: Study theoretically about internal marketing campaigns and business incentives; observe how these campaigns are detrimental to their collaborators; understand which speeches are disseminated by such campaigns. As a methodological procedure, we undertook an exploratory study, regarding Campaigns and Commercial Incentives in a food company in such a way, we understand as a methodological procedure the use of observational research, with a focus on such campaigns, observing how these employees who belong to such company, receive this content and add this strategy to the respective organization. Ademias, we demonstrate the functionality of Promotional Campaigns and Sales Incentives in a food company, their functions and contributions to its marketing and commercial strategy, in addition to being able to understand what are the benefits that a company guarantees when working with this internal marketing strategy and incentive campaigns.